Présentation d’une controverse : les Écritures face à la critique biblique au xixe siècle en Grande-Bretagne - Frédéric Slaby (Revue LISA)
Until the beginning of the 19th century, most of the Catholic, Anglican and Protestant exegetes, theologians and regular churchgoers thought that the Bible was the Word of God, and that God’s truth was present in every word of the Scriptures. Thereafter, biblical studies had to deal with questions that had emerged from the intellectual explosion and scholarly revolution of the previous centuries, and that were still very difficult to handle in their relationship with the Scriptures. The controversy around the authority of the Bible gained ever-increasing momentum as the century unfolded, and was responsible for the division of Bible scholars into two or three major groups whose general conclusions revealed the dynamic element in their studies and interpretation of the Bible. As the positivist and “liberal” critics privileged the use of reason in their approach, it comes as no surprise that the natural or human aspect should be taken into greater consideration by them than by the “orthodox” and “traditionalist” thinkers who privileged the use of faith and took into account the supernatural or divine aspect in their study of the Bible. Although the inerrancy of the Bible sometimes underlies textual, literary or historical discoveries, or matters of inspiration and divine revelation in the Scriptures, this article will identify elements of change and continuity as regards biblical inerrancy.